Australian and New Zealand doctors' experiences of disciplinary notifications, investigations, proceedings and interventions relating to alleged mental health impairment: a qualitative analysis of interviews. (January 2023) - Bradfield, Owen; Jenkins, Kym; Spittal, Matthew; Bismark, Marie
Abstract: When poor mental health impairs a doctor's ability to safely practise medicine, poor patient outcomes can result. Medical regulators play a critical role in protecting the public from impaired doctors, by requiring monitoring and treatment. However, regulatory processes may paradoxically harm doctors, with potential adverse implications for the community. There is little prior research examining the experiences of doctors with prior mental health or substance use challenges who are subject to regulatory notifications and processes relating to their health. Therefore, we explored this issue through the thematic analysis of semi-structured qualitative interviews. Participants reported that mandated treatment improved aspects of their health, but that fear of regulatory processes delayed them seeking treatment. Participants recognised being significantly unwell at the time of regulatory notification. Participants told us that regulatory processes triggered psychological distress, symptom relapse, and adverse financial and vocational implications. They also told us that these processes eroded their trust in regulators and regulatory processes. To improve health outcomes for unwell doctors and to create safer healthcare for the community, we propose: 1) greater awareness and education of the medical profession about the thresholds and requirements for mandatory reporting of health impairment; 2) better integrating specialised doctors' health services into existing regulatory pathways; and 3) adoption of a more therapeutic approach to regulation by medical regulators.